Growth Response of Maize to Crotalaria Weed Manures - S. N. Shinde2 and B. Jadhav3, D. R. Chamle1*, (Recent Research in Science and Technology, 2010)
Abstract A field experiment was conducted at Dr. Babasaheb Ambedkar Marathwada University, Aurangabad to evaluate the performance of Crotalaria weed manures viz. green manure (GM), compost (CM), vermicompost (VM) and dry leaf manure (DM) on the productivity and nutrient uptake of maize. For comparison, mineral fertilizers were also applied at a rate of 120, 80 and 40 kg N, P and K ha-1 respectively. The observations were recorded on morph-physiological traits at 101 days after sowing (DAS). On the basis of the results obtained, it is concluded that the application of compost (CM) was more effective in increasing the yield and nutrient contents of maize as compared to other treatments. Keywords: Crotalaria, Green manure, Compost, Vermicompost, Dry leaf manure, Maize